Anode material, electrode piece containing said anode material and electrochemical device
The silicon monoxide-based negative electrode material with a surface-to-interior oxygen gradient and conductive coating addresses conductivity and expansion issues, enhancing the stability and cycle performance of lithium ion batteries.
Patent Information
- Application Number
- JP2023538961
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2020-12-28
- Publication Date
- 2024-12-25
- Estimated Expiration
- 2040-12-28
AI Technical Summary
Silicon-based negative electrode materials for lithium ion batteries face issues of low electrical conductivity and significant volumetric expansion during charging and discharging, hindering their application in high-energy density batteries.
A negative electrode material composed of silicon monoxide particles with a gradient molar ratio of oxygen to silicon, where the surface molar ratio exceeds 1.5 times the interior ratio, combined with a conductive material and optional polymer coating, to enhance stability and conductivity.
The material reduces volumetric expansion and improves cycle performance, maintaining high energy density and stability in lithium ion batteries.
Smart Images

Figure 0007606615000012 
Figure 0007606615000013 
Figure 0007606615000001
Abstract
Description
[Technical field]
[0001] The present invention relates to the field of electrochemistry, and in particular to negative electrode materials, pole pieces and electrochemical devices containing said negative electrode materials. [Background technology]
[0002] Lithium-ion batteries have the characteristics of large specific energy, high operating voltage, low self-discharge rate, small volume, and light weight, and are widely used in consumer electronics. With the rapid development of electric vehicles and portable electronic devices, the requirements for the energy density and cycle performance of lithium-ion batteries are becoming higher and higher. Silicon-based anode materials have a high capacity per gram of 1500mAh / g~2000mAh / g, and are considered to be the next-generation lithium-ion anode material with the most promising applications.
[0003] However, silicon-based anode materials have problems such as relatively low electrical conductivity and large volume expansion during charging and discharging, which have hindered their further application in lithium-ion batteries. Therefore, there is a need for silicon-based anode materials that can further improve the cycle stability of lithium-ion batteries and further reduce their volume expansion. Summary of the Invention
[0004] The present invention aims to provide an anode material, a pole piece containing the anode material, and an electrochemical device, in order to reduce the volume expansion of the electrochemical device and improve the cycle performance of the electrochemical device.
[0005] In the following description of the present invention, a lithium ion battery is used as an example of an electrochemical device to explain the present invention, but the electrochemical device of the present invention is not limited to a lithium ion battery.
[0006] The specific technical proposals are as follows: A first aspect of the present invention provides an anode material comprising silicon monoxide particles, wherein a molar ratio A of oxygen to silicon at the surface of the silicon monoxide particle is greater than a molar ratio B of oxygen to silicon inside the silicon monoxide particle, such that the molar ratio A of oxygen to silicon at the surface of the silicon monoxide particle and the molar ratio B of oxygen to silicon at any point 25 nm or more away from the surface of the silicon monoxide particle satisfy A / B>1.5.
[0007] In the anode material of the present invention, the molar ratio A of oxygen to silicon on the surface of the silicon monoxide particle is greater than the molar ratio B of oxygen to silicon inside the silicon monoxide particle, so that the oxygen content on the surface of the silicon monoxide particle is higher than the oxygen content inside the silicon monoxide particle. The molar ratio A of oxygen to silicon on the surface of the silicon monoxide particle and the molar ratio B of oxygen to silicon at any one point that is 25 nm or more away from the surface of the silicon monoxide particle satisfy A / B>1.5, so that the anode material of the present invention has a relatively low lithium insertion expansion performance and improves the stability of the anode material. In the present invention, the molar ratio of oxygen to silicon gradually decreases from the surface to the inside of the silicon monoxide particle according to a gradient.
[0008] In the present invention, the "molar ratio of oxygen to silicon" means the ratio of the number of oxygen and silicon atoms in a silicon monoxide particle, that is, the molar ratio of oxygen element to silicon element.
[0009] In one embodiment of the present invention, the molar ratio B of oxygen to silicon in the silicon monoxide particles satisfies 0.5≦B≦1.5. Without being limited by any theory, when the molar ratio B of oxygen to silicon in the silicon monoxide particles satisfies 0.5≦B≦1.5, the negative electrode material has a lower lithium insertion expansion performance, thereby improving the stability of the negative electrode material. The lower limit of the molar ratio B of oxygen to silicon in the silicon monoxide particles may include 0.5, 0.7, 0.8, 0.9, or 1.0, while the upper limit of the molar ratio B of oxygen to silicon in the silicon monoxide particles may include 1.1, 1.2, 1.3, 1.4, or 1.5.
[0010] In one embodiment of the present invention, the surface of the silicon monoxide particles further includes a conductive material to improve the conductivity of the negative electrode material, and the thickness of the conductive material is 1 nm to 50 nm. Without being limited by any theory, if the thickness of the conductive material is too small, for example, less than 1 nm, it is difficult to effectively improve the conductivity of the negative electrode material. If the thickness of the conductive material is too large, for example, more than 50 nm, it will reduce the relative content of active material in the negative electrode piece, thereby affecting the energy density of the lithium ion battery. The lower limit of the thickness of the conductive material may include 1 nm, 5 nm, 10 nm, 20 nm, or 25 nm, while the upper limit of the thickness of the conductive material may include 30 nm, 35 nm, 40 nm, 45 nm, or 50 nm.
[0011] In the present invention, the conductive material is not particularly limited as long as it can further improve the conductivity of the negative electrode material. For example, the conductive material may include at least one of amorphous carbon, carbon nanotubes, graphene, and vapor-deposited carbon fibers.
[0012] In one embodiment of the present invention, based on the total mass of the negative electrode material, the mass percentage of the conductive material is 0.5%-8%. Without being limited by any theory, if the content of the conductive material is too low, for example, less than 0.5%, it is difficult to effectively improve the conductivity of the negative electrode material. If the content of the conductive material is too high, for example, more than 8%, it will affect the energy density of the lithium ion battery by reducing the relative content of the active material in the negative electrode piece. The lower limit of the content of the conductive material of the present invention may include 0.5%, 1%, 2%, 3%, or 4%, while the upper limit of the content of the conductive material may include 5%, 6%, 7%, or 8%.
[0013] In one embodiment of the present invention, the silicon monoxide particles further have a polymer on the surface. The silicon monoxide particles may have a polymer on at least a part of the surface, or may have the entire surface covered with the polymer. Without being limited to any theory, the polymer itself generally has good structural stability and also functions as a carrier for the conductive material.
[0014] In the present invention, based on the total mass of the negative electrode material, the mass percentage of the polymer is 1% to 10%. Without being limited by any theory, if the polymer content is too low, for example, less than 1%, it is difficult to effectively improve the structural stability of the negative electrode material. If the polymer content is too high, for example, more than 10%, it will affect the energy density of the lithium ion battery by reducing the relative content of the active material in the negative electrode piece. The lower limit of the polymer mass percentage may include 1%, 2%, 3%, or 4%, while the upper limit of the polymer mass percentage may include 5%, 6%, 7%, 8%, or 10%.
[0015] The polymer of the present invention is not particularly limited as long as it can achieve the object of the present invention. In one embodiment of the present invention, the polymer may include at least one of carboxymethyl cellulose, polyacrylic acid, polyethylene alcohol, polyamide, polyacrylate, and derivatives thereof. The polymer may be used alone or in combination of two or more kinds in any ratio.
[0016] In one embodiment of the present invention, the silicon monoxide particles have a Dv50 of 1 μm to 15 μm. Without being limited to any theory, the stability of the negative electrode material can be further improved by controlling the Dv50 of the silicon monoxide particles within the above range. Dv50 represents a particle size at which the particles have a volume cumulative 50% from the small particle size side in a volume-based particle size distribution. The lower limit of the Dv50 of the silicon monoxide particles may include 1 μm, 3 μm, 5 μm, or 7 μm, while the upper limit of the Dv50 of the silicon monoxide particles may include 9 μm, 10 μm, 12 μm, or 15 μm.
[0017] In one embodiment of the present invention, the negative electrode material may further include amorphous carbon. Specifically, silicon monoxide particles may be dispersed in a matrix of amorphous carbon to form a silicon monoxide-amorphous carbon composite material, which further improves the electrical conductivity of the negative electrode material.
[0018] In one embodiment of the present invention, the Dv50 of the negative electrode material is 3 μm to 15 μm. Without being limited by any theory, if the Dv50 of the negative electrode material is too small (e.g., less than 3 μm), the specific surface area of the small particles is large, so the negative electrode material is more likely to react with the electrolyte and generate more by-products. If the Dv50 of the negative electrode material is too large (e.g., more than 15 μm), the large particles have a large volume change during cycling, and the negative electrode material is more likely to be crushed, which is disadvantageous to improving the stability of the negative electrode material.
[0019] In one embodiment of the present invention, the Dv99 of the negative electrode material is 10 μm to 45 μm, which indicates that the particle size distribution of the negative electrode material is uniform, thereby reducing the roughness of the negative electrode piece surface and improving the performance of the negative electrode piece. Dv99 indicates the particle size at which the volume cumulative 99% of the negative electrode material is from the small particle size side in the volume-based particle size distribution.
[0020] In one embodiment of the present invention, the Dv50 of the silicon monoxide particles in the negative electrode material is 60nm to 500nm. In the present invention, the lower limit of the Dv50 of the silicon monoxide particles in the negative electrode material may include 60nm, 100nm, 150nm, 200nm or 250nm, while the upper limit of the Dv50 of the silicon monoxide particles in the negative electrode material may include 300nm, 350nm, 400nm, 450nm or 500nm.
[0021] In one embodiment of the present invention, the capacity per gram of the negative electrode material at 2.0 V is 600 mAh / g to 1400 mAh / g, indicating that the negative electrode material of the present invention has a high capacity per gram.
[0022] In one embodiment of the present invention, the mass percentage of carbon is 5% to 50% based on the total mass of the negative electrode material. Without being limited by any theory, if the carbon content is too low (e.g., less than 5%), it is disadvantageous to improve the electrical conductivity of the negative electrode material. If the carbon content is too high (e.g., more than 50%), it is disadvantageous to improve the energy density of the lithium ion battery. By controlling the carbon content in the negative electrode material of the present invention within the above range, the negative electrode material can have good electrical conductivity performance and the lithium ion battery can have high energy density. In the present invention, the lower limit of the mass percentage of carbon may include 5%, 10%, 15%, 20% or 25%, while the upper limit of the mass percentage of carbon may include 30%, 35%, 40%, 45% or 50%.
[0023] In one embodiment of the present invention, based on the total mass of the negative electrode material, the mass percentage of silicon is 15% to 38%. Without being limited by any theory, if the silicon content is too low (e.g., less than 15%), it is disadvantageous to improve the energy density of the lithium ion battery, and if the silicon content is too high (e.g., more than 38%), it is disadvantageous to improve the stability of the negative electrode material. By controlling the silicon content in the negative electrode material of the present invention within the above range, the negative electrode material can have good stability and the lithium ion battery can have high energy density. In the present invention, the lower limit of the mass percentage of silicon may include 15%, 20%, 23% or 25%, while the upper limit of the mass percentage of silicon may include 27%, 30%, 35% or 38%.
[0024] There is no limitation on the method for producing the negative electrode material of the present invention, and any method known to those skilled in the art, for example, the following method, can be used.
[0025] Silica and metal silicon powder are mixed in a molar ratio of 1:5 to 5:1 to obtain a mixture. -4 kPa~10 -1 The mixture was heated at a temperature range of 1200°C to 1450°C for 0.5 to 24 hours under conditions of 100 kPa to obtain a gas. The gas was then cooled to obtain a solid, which was then crushed and sieved to obtain silicon monoxide particles with different particle size distributions.
[0026] The obtained silicon monoxide particles were placed in an inert atmosphere with an oxygen content of less than 5% by volume, and heat-treated at 250° C. to 700° C. for 0.5 hours to 12 hours to obtain a negative electrode material.
[0027] Alternatively, the obtained silicon monoxide particles are placed in a sand mill containing an organic solvent (e.g., absolute ethanol) and a dispersant (e.g., asphalt) and ball milled for 2 to 48 hours, and the oxide layer on the surface of the silicon monoxide particles is oxidized to the organic solvent or naturally oxidized to the atmosphere.
[0028] By further adding a conductive material to the surface of the silicon monoxide particles, a conductive layer can be formed, and the conductive layer can be formed by the following method. Silicon monoxide particles are placed in a chemical vapor deposition (CVD) furnace and vapor-deposited using hydrocarbon gases such as methane, acetylene, and ethylene at a temperature of 600°C to 900°C. After vapor deposition, the product may be subjected to post-treatment such as classification and demagnetization.
[0029] Alternatively, silicon monoxide particles, a conductive material, and a dispersant are thoroughly dispersed in an organic solvent, stirred, and the organic solvent is removed to obtain a solid powder, that is, a conductive layer is formed on the surface of the silicon monoxide particles. The solid powder may be subjected to post-treatment such as pulverization, sieving, demagnetization, and calcination.
[0030] In the present invention, the organic solvent is not particularly limited, and may be, for example, anhydrous ethanol, and may be used to oxidize the surface of silicon monoxide particles to form an oxide layer. The amount of organic solvent added is not particularly limited, and for example, the mass ratio of organic solvent to silicon monoxide particles is 1:20 to 1:30.
[0031] The amount of dispersant added is not particularly limited as long as the silicon monoxide particles are sufficiently dispersed in the organic solvent, and for example, the mass ratio of dispersant to silicon monoxide particles is 0.5-3:97-99.5.
[0032] The inert atmosphere is not particularly limited, and is, for example, argon gas or helium gas.
[0033] A second aspect of the present invention provides an anode piece comprising the anode material according to any one of the previous embodiments.
[0034] The positive electrode piece of the present invention is not limited as long as it can achieve the object of the present invention. For example, the positive electrode piece generally includes a positive electrode current collector and a positive electrode active material layer. The positive electrode current collector is not limited and may include any positive electrode current collector known in the art, such as aluminum foil, aluminum alloy foil, or composite current collector. The positive electrode active material layer includes a positive electrode active material, and the positive electrode active material is not limited and may include any positive electrode active material known in the art, such as at least one of nickel cobalt manganese oxide (811, 622, 523, 111), nickel cobalt lithium aluminum oxide, lithium iron phosphate, lithium-rich manganese-based material, lithium cobalt oxide, lithium manganese oxide, lithium manganese iron phosphate, and lithium titanate.
[0035] The separator of the present invention may include at least one selected from polyethylene, polypropylene, polyethylene terephthalate, polyamide and aramid, but is not limited thereto. For example, polyethylene includes at least one component selected from high density polyethylene, low density polyethylene and ultra-high molecular weight polyethylene. In particular, polyethylene and polypropylene have good effect in preventing short circuit, and can improve the stability of lithium ion battery by cut-off effect.
[0036] The separator may further include a porous layer on at least one surface of the separator. The porous layer includes inorganic particles and a binder, and the inorganic particles are one or more selected from alumina (Al2O3), silica (SiO2), magnesium oxide (MgO), titanium oxide (TiO2), hafnium dioxide (HfO2), tin oxide (SnO2), cerium dioxide (CeO2), nickel oxide (NiO), zinc oxide (ZnO), calcium oxide (CaO), zirconium oxide (ZrO2), yttrium oxide (Y2O3), silicon carbide (SiC), boehmite, aluminum hydroxide, magnesium hydroxide, calcium hydroxide, and barium sulfate. The binder is one or a combination of a plurality of materials selected from polyvinylidene fluoride, vinylidene fluoride-hexafluoropropylene copolymer, polyamide, polyacrylonitrile, polyacrylic acid ester, polyacrylic acid, polyacrylate, sodium carboxymethylcellulose, polyvinylpyrrolidone, polyvinyl ether, polymethyl methacrylate, polytetrafluoroethylene, and polyhexafluoropropylene.
[0037] The porous layer can improve the heat resistance, oxidation resistance and electrolyte infiltration performance of the separator, and can increase the adhesion between the separator and the positive electrode or the negative electrode.
[0038] The lithium ion battery of the present invention further includes an electrolyte, which may be one or more of a gel electrolyte, a solid electrolyte, and an electrolyte solution, the electrolyte solution including a lithium salt and a non-aqueous solvent.
[0039] In some embodiments of the present invention, the lithium salt is one or more selected from LiPF6, LiBF4, LiAsF6, LiClO4, LiB(CH5)4, LiCH3SO3, LiCF3SO3, LiN(SO2CF3)2, LiC(SO2CF3)3, LiSiF6, LiBOB, and lithium difluoroborate. For example, LiPF6 can be used since it provides high ionic electrical conductivity and can improve cycle performance.
[0040] The non-aqueous solvent may be a carbonate ester compound, a carboxylate compound, an ether compound, another organic solvent, or a combination thereof.
[0041] The carbonate ester compound may be a chain carbonate ester compound, a cyclic carbonate ester compound, a fluorocarbonate ester compound, or a combination thereof.
[0042] Examples of the linear carbonate ester compound are dimethyl carbonate (DMC), diethyl carbonate (DEC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), methyl ethyl carbonate (MEC), and combinations thereof. Examples of the cyclic carbonate ester compound are ethylene carbonate (EC), propylene carbonate (PC), butylene carbonate (BC), vinyl ethylene carbonate (VEC), and combinations thereof. Illustrative examples of fluorocarbonate compounds are fluoroethylene carbonate (FEC), 1,2-difluoroethylene carbonate, 1,1-difluoroethylene carbonate, 1,1,2-trifluoroethylene carbonate, 1,1,2,2-tetrafluoroethylene carbonate, 1-fluoro-2-methylethylene carbonate, 1-fluoro-1-methylethylene carbonate, 1,2-difluoro-1-methylethylene carbonate, 1,1,2-trifluoro-2-methylethylene carbonate, trifluoromethylethylene carbonate, and combinations thereof. Illustrative examples of the carboxylate compounds are methyl formate, methyl acetate, ethyl acetate, n-propyl acetate, tert-butyl acetate, methyl propionate, ethyl propionate, propyl propionate, gamma-butyrolactone, decalactone, valerolactone, mevalonolactone, caprolactone, and combinations thereof.
[0043] Illustrative examples of the ether compounds are dibutyl ether, tetraethylene glycol dimethyl ether, diethylene glycol dimethyl ether, 1,2-dimethoxyethane, 1,2-diethoxyethane, ethoxymethoxyethane, 2-methyltetrahydrofuran, tetrahydrofuran, and combinations thereof.
[0044] Examples of such other organic solvents are dimethyl sulfoxide, 1,2-dioxolane, sulfolane, methyl sulfolane, 1,3-dimethyl-2-imidazolidinone, N-methyl-2-pyrrolidone, formamide, dimethylformamide, acetonitrile, trimethyl phosphate, triethyl phosphate, trioctyl phosphate, and phosphate esters, and combinations thereof.
[0045] A third aspect of the present invention provides an electrochemical device comprising a negative electrode piece according to the second aspect.
[0046] A fourth aspect of the present invention provides an electronic device comprising an electrochemical device according to the third aspect.
[0047] The electronic device of the present invention is not particularly limited and may be any electronic device existing in the prior art. In some embodiments, the electronic device may include, but is not limited to, a notebook computer, a pen-input computer, a mobile computer, an electronic book player, a mobile phone, a portable fax machine, a portable copy machine, a portable printer, a stereo headphone, a video recorder, a liquid crystal television, a portable cleaner, a portable CD player, a mini disk, a walkie-talkie, an electronic notepad, a calculator, a memory card, a portable recorder, a radio, a backup power source, a motor, an automobile, a motorcycle, an electric assist bicycle, a bicycle, a lighting device, a toy, a game machine, a clock, an electric tool, a flash, a camera, a large-scale household storage battery, and a lithium-ion capacitor.
[0048] The manufacturing process of the electrochemical device is well known to those skilled in the art, and the present invention is not particularly limited thereto. For example, the electrochemical device can be manufactured by stacking the positive electrode and the negative electrode via the separator provided by the present invention, winding and folding the stack as necessary, placing the stack in a case, injecting an electrolyte into the case, and sealing the case. In addition, an overcurrent prevention element, a guide plate, etc. can be placed in the case as necessary to prevent pressure rise and overcharging and discharging inside the electrochemical device.
[0049] The present invention provides an anode material, a pole piece and an electrochemical device comprising the anode material, the anode material comprising silica particles, the molar ratio A of oxygen to silicon on the surface of the silicon monoxide particles being greater than the molar ratio B of oxygen to silicon inside the silicon monoxide particles, thereby enhancing the surface stability of the anode material. The molar ratio A of oxygen to silicon on the surface of the silicon monoxide particles and the molar ratio B of oxygen to silicon at any point 25 nm or more away from the surface of the silicon monoxide particles satisfy A / B>1.5, thereby improving the surface stability of the anode material and improving the ion transmission performance of the anode material, so that the electrochemical device comprising the anode material has a smaller volume expansion during charging and discharging cycles and has better cycle performance. [Brief description of the drawings]
[0050] In order to more clearly describe the technical solutions of the present invention and the prior art, the following briefly describes the embodiments and drawings necessary for the prior art, but obviously, the drawings described below are only some embodiments of the present invention. [Figure 1] FIG. 1 is a FIB-TEM line scan element distribution map of Example 7 of the present invention. [Diagram 2] FIG. 2 is a FIB-TEM line scan element distribution diagram of Comparative Example 1 of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0051] In order to clearly show the objectives, technical solutions and advantages of the present invention, the present invention will be described in more detail below with reference to the drawings and embodiments. It is clear that the described embodiments are only some of the embodiments of the present invention, and do not include all of the embodiments. All other technical solutions obtained by those skilled in the art based on the embodiments of the present invention are within the scope of the claims of the present invention.
[0052] In the embodiments of the present invention, a lithium ion battery is used as an example of an electrochemical device to describe the present invention, but the electrochemical device of the present invention is not limited to a lithium ion battery. EXAMPLES
[0053] Hereinafter, the embodiments of the present invention will be described in more detail with reference to examples and comparative examples. Various types of tests and evaluations are performed as follows. Unless otherwise specified, "parts" and "%" are based on mass.
[0054] Measurement method and equipment Measuring the performance of negative electrode material powder Micromorphology observation of negative electrode material powder particles: A scanning electron microscope was used to observe the micromorphology of the negative electrode material powder. The measuring device used was an OXFORD EDS (X-max-20mm 2 ) with an accelerating voltage of 10 KV. By adjusting the focal length, high-magnification observations were performed from 50 K, and at low magnifications of 500 to 2000, the aggregation state of the negative electrode material particles was mainly observed.
[0055] Measurement of the specific surface area of negative electrode materials After measuring the amount of gas adsorbed onto the solid surface at different relative pressures, the adsorption amount of the sample monolayer was calculated using the Brownauer-Emmett-Teller adsorption theory and its formula (BET formula), and the specific surface area of the negative electrode material was calculated.
[0056] BET Official:
number
[0057] In the formula, W is the mass of gas adsorbed by the solid sample at the relative pressure, Wm is the amount of gas adsorbed saturated with one monolayer, (c-1) / (WmC) is the slope, and 1 / WmC is the intercept. The total surface area St is St = (Wm × N × Acs / M), the specific surface area S is S = St / m, m is the mass of the sample, and Acs is the average area occupied by one N2 molecule of 16.2A. 2 This indicates that.
[0058] The measurement was performed after weighing 1.5 g to 3.5 g of a powder sample of the negative electrode material, placing it in a measurement sample tube of a specific surface area and porosity analyzer (model number: TriStar II 3020), and degassing it at 200° C. for 120 minutes.
[0059] Measuring particle size of negative electrode materials 0.02 g of a powder sample of the negative electrode material was placed in a clean 50 ml beaker, 20 ml of deionized water was added, and 3 to 5 drops of a surfactant with a mass concentration of 1% were then added. The powder sample was then completely dispersed in the water, after which it was subjected to ultrasonic vibration for 5 minutes in an ultrasonic cleaner with an output of 120 W, and the particle size distribution was measured using a laser particle size analyzer (model number: MasterSizer 2000).
[0060] Measurement of tap density of negative electrode materials The Chinese national standard GB / T 5162-2006 "Determination of tap density of metal powders" was adopted.
[0061] Measurement of carbon content in anode materials The negative electrode material sample was heated to high temperature in a high frequency furnace under oxygen-rich conditions to burn the carbon and oxidize it to carbon dioxide gas. After the gas was processed, it entered the corresponding absorption tank, absorbed the corresponding infrared radiation, and converted into the corresponding signal through the detector. The signal was collected by a computer, and after linearity correction, it was converted into a value proportional to the concentration of carbon dioxide gas. The values in the entire analysis process were integrated. After the analysis was completed, the computer divided the integrated value by the weight value, multiplied by the correction factor, and subtracted the blank to obtain the carbon percentage content in the sample. The sample was measured using a high frequency infrared carbon-sulfur analyzer (model: HCS-140 manufactured by Shanghai Dekai Instrument Co., Ltd.).
[0062] Measurement of atomic ratios on the surface of negative electrode materials A conductive adhesive containing a negative electrode material was spread on copper foil, and the cut cross section was milled with a plasma milling machine (Leica EM TIC 3X-Ion Beam Slope Cutter), then set in a scanning electron microscope (SEM) to find the cut silicon monoxide particles, and the silicon monoxide particles were cut in the vertical direction of the cross section with a focused ion beam (FIB) to obtain cross-sectional flakes (about 50 nm) containing silicon monoxide particles, which were then measured with a transmission electron microscope (TEM) and EDS analysis was performed on points A' randomly taken at a location 1 to 2 nm from the outer surface. That is, the Si:O atomic ratio on the outer surface of the silicon monoxide particle was defined as A, and the Si:O atomic ratio at B', which extends perpendicularly to the outer surface from this point A' to the inside of the silicon monoxide particle and is more than 25 nm from the outer surface of point A', was defined as B.
[0063] Measuring the initial efficiency of button cells Each negative electrode material prepared in the examples and comparative examples was mixed with conductive carbon black and polymer in a ratio of 80:10:10, and deionized water was added and stirred to form a slurry. A coating layer of 100 μm was applied to the surface of a current collector using a doctor blade, and the surface was dried in a vacuum drying box at 85°C for 12 hours. The surface was then cut into wafers with a diameter of 1 cm using a punching machine in a dry environment. A button cell was assembled in a glove box using a metal lithium sheet as a counter electrode and a Ceglard composite film as a separator, and electrolyte was added. The battery was measured for charge and discharge using a LAND series battery measurement system. The initial efficiency was calculated as the capacity at a discharge cut-off voltage of 2.0V / capacity at a charge cut-off voltage of 0.005V.
[0064] How to Calculate the Capacity per Gram of a Button Cell This is the capacity per gram of the button cell at a discharge gut-off voltage of 2.0V.
[0065] Measuring the performance of all batteries Cycle performance measurement The measurement temperature was 25°C or 45°C, and the battery was charged at a constant current of 0.7C until it reached 4.4V, then charged at a constant voltage of 0.025C, and allowed to stand for 5 minutes, after which it was discharged at 0.5C until it reached 3.0V. The capacity obtained in this step was taken as the initial capacity, and one cycle was performed by charging at 0.7C / discharging at 0.5C. The capacity decay curve was obtained by determining the ratio of the capacity at each step to the initial capacity. The number of cycles required to cycle until the capacity retention rate reached 90% at 25°C was taken as the cycle characteristics of the battery at room temperature, and the number of cycles required to cycle until the capacity retention rate reached 80% at 45°C was taken as the cycle characteristics of the battery at high temperature. The cycle characteristics of the materials were compared by comparing the number of cycles in the above two cases.
[0066] Measurement of the expansion rate of a lithium-ion battery when fully charged The thickness of the lithium-ion battery when it is half charged, i.e., at 50% state of charge (SOC), is measured with a micrometer. When the battery reaches 400 cycles, it is fully charged, i.e., at 100% SOC, and the thickness of the lithium-ion battery at this time is measured again with a micrometer. By comparing this with the thickness of the lithium-ion battery at the initial half charge, the full charge expansion rate of the lithium-ion battery at this time is obtained.
[0067] Working Example Example 1 <Preparation of negative electrode material> Silica and metal silicon powder were mixed in a molar ratio of 1:1 to obtain a mixture. -4 The mixture was heated for 10 hours under conditions of 1,400°C and 1 kPa to obtain a gas, which was then cooled to obtain a solid. The solid was then crushed and sieved to obtain silicon monoxide (SiO) particles with a Dv50 of 5.2 μm. Silicon monoxide particles were placed in argon gas with an oxygen content of less than 5% by volume and heat-treated at 400°C for 10 hours to obtain a negative electrode material with an oxide layer having a thickness of 22 nm.
[0068] <Preparation of button cells> The obtained negative electrode material, conductive carbon black, and polypropylene alcohol (PAA) binder were mixed in a ratio of 80:10:10, and after adding deionized water, the mixture was stirred to make a slurry with a solid content of 40%. A coating layer of 100 μm in thickness was applied to the surface of the current collector using a doctor blade, and the surface was dried in a vacuum drying box at 85°C for 12 hours. After that, the surface was cut into a round sheet with a diameter of 1 cm using a punching machine in a dry environment. A button cell was assembled in a glove box by adding an electrolyte solution to a metal lithium sheet as a counter electrode and a Ceglard composite film as a separator.
[0069] <Making a complete battery> <Preparation of negative electrode piece> Graphite, the obtained negative electrode material, conductive agent (conductive carbon black) and binder (PAA) were mixed in a mass ratio of 70:15:5:10, and then deionized water was added as a solvent to prepare a slurry with a solid content of 60%, and an appropriate amount of deionized water was added to adjust the viscosity of the slurry to 5000 Pa·s to prepare a negative electrode slurry. The obtained negative electrode slurry was applied to one surface of a copper foil with a thickness of 8 μm, dried at 110 ° C, and cold pressed to obtain a negative electrode piece with a coating layer thickness of 100 μm. The above coating step was then repeated on the other surface of this negative electrode piece to obtain a negative electrode piece with a negative electrode active material layer applied on both sides. The negative electrode piece was cut to a size of 74 mm × 867 mm, and a tab was welded.
[0070] <Preparation of positive electrode piece> After mixing the positive electrode active material lithium cobalt oxide, conductive carbon black, and polyvinylidene fluoride (PVDF) in a mass ratio of 95:2.5:2.5, N-methylpyrrolidone (NMP) was added as a solvent to prepare a slurry with a solid content of 75%, and the mixture was stirred uniformly. The slurry was applied to one surface of an aluminum foil with a thickness of 12 μm, dried at 90° C., and cold pressed to obtain a positive electrode piece with a positive electrode active material layer thickness of 110 μm. The above coating step was then repeated on the other surface of this positive electrode piece to obtain a positive electrode piece with a positive electrode active material layer applied on both sides. The positive electrode piece was cut to a size of 76 mm×851 mm, and a tab was welded.
[0071] <Preparation of separator> A 15 μm thick porous polyethylene (PE) polymer film was used as the separator.
[0072] <Preparation of electrolyte> In an environment with a water content of less than 10 ppm, non-aqueous organic solvents propylene carbonate (PC), ethylene carbonate (EC), and diethyl carbonate (DEC) were mixed in a mass ratio of 1:1:1, and then lithium hexafluorophosphate (LiPF6) was added and dissolved in the non-aqueous organic solvent, mixed uniformly, and then fluorinated vinyl carbonate (FEC) was added to obtain an electrolyte. The molar concentration of LiPF6 in the electrolyte was 1.15 mol / L, and the mass concentration of FEC in the electrolyte was 12.5%.
[0073] <Making a lithium-ion battery> The positive electrode, separator, and negative electrode pieces prepared above were stacked in order, a separator was placed between the positive electrode and negative electrode pieces to provide isolation, and the stack was wound up to obtain an electrode module. The electrode module was placed in an aluminum plastic packaging bag, moisture was removed at 80°C, the mixed electrolyte was injected, and a lithium-ion battery was obtained through processes such as vacuum sealing, standing, formation, and shaping.
[0074] Example 2 <Preparation of negative electrode material> was the same as in Example 1, except that the heat treatment time was changed to 5 hours.
[0075] Example 3 <Preparation of negative electrode material> was the same as in Example 1, except that the heat treatment time was changed to 0.5 hours.
[0076] Example 4 In <Preparation of negative electrode material>, the same procedure as in Example 2 was followed except that the Dv50 of silicon monoxide was 1.3 μm.
[0077] Example 5 In <Preparation of negative electrode material>, the same procedure as in Example 2 was followed except that the Dv50 of silicon monoxide was 14.6 μm.
[0078] Example 6 The procedure is the same as in Example 1, except for the difference in <Preparation of negative electrode material>. <Preparation of negative electrode material> The silicon monoxide particles prepared in Example 1 were put into a sand mill containing anhydrous ethanol and asphalt as a dispersant and ball-milled for 24 hours, the Dv50 of the silicon monoxide particles was 110 nm, the surface of the silicon monoxide particles was oxidized in the solution to form an oxide layer with a thickness of 23 nm, and the mixture was dried to obtain a negative electrode material. The mass ratio of the asphalt to the silicon monoxide particles was 1:99, and the mass ratio of the anhydrous ethanol to the silicon monoxide particles was 1:5.
[0079] Example 7 <Preparation of negative electrode material> was the same as in Example 6, except that the Dv50 of the silicon monoxide particles was changed to 190 nm and the ball mill time was changed to 12 hours.
[0080] Example 8 <Preparation of negative electrode material> was the same as in Example 6, except that the Dv50 of the silicon monoxide particles was changed to 520 nm and the ball milling time was changed to 8 hours.
[0081] Example 9 In <Preparation of negative electrode material>, the same procedure as in Example 6 was repeated except that the Dv50 of the silicon monoxide particles was changed to 80 nm and the ball mill time was changed to 48 hours.
[0082] Example 10 The procedure is the same as in Example 2, except for the difference in <Preparation of negative electrode material>. <Preparation of negative electrode material>
[0083] The negative electrode material obtained in Example 2 was used as the base material, and the base material, amorphous carbon as a conductive material, and carboxymethyl cellulose as a dispersant were dispersed in absolute ethanol in a mass ratio of 96:3.2:0.8, and the mixture was stirred uniformly at room temperature, after which the absolute ethanol was removed to obtain a solid. The obtained solid was pulverized and sieved to obtain a negative electrode material.
[0084] Example 11 The same procedure as in Example 10 was repeated except that in <Preparation of negative electrode material>, carbon nanotubes were used as the conductive material, and the mass ratio of the base material, conductive material, and dispersant was 96.1:3.1:0.8. The aspect ratio of the carbon nanotubes was 3,000.
[0085] Example 12 <Preparation of negative electrode material> was the same as in Example 10, except that graphene was used as the conductive material and the mass ratio of the base material, conductive material, and dispersant was 95.2:4.0:0.8.
[0086] Example 13 <Preparation of negative electrode material> was the same as in Example 10, except that vapor-deposited carbon fiber was used as the conductive material and the mass ratio of the substrate, conductive material, and dispersant was 91.2:8.0:0.8.
[0087] Example 14 <Preparation of negative electrode material> was the same as in Example 10, except that the mass ratio of the base material, conductive material, and dispersant was 98.7:0.5:0.8.
[0088] Example 15 The procedure was the same as in Example 6, except for the difference in <Preparation of negative electrode material>. <Preparation of negative electrode material> The negative electrode material obtained in Example 6 was used as the substrate, and the substrate and amorphous carbon were dispersed in anhydrous ethanol in a mass ratio of 88:12, and the mixture was stirred uniformly at room temperature, after which the anhydrous ethanol was removed to obtain a solid. The obtained solid was pulverized and sieved to obtain a negative electrode material.
[0089] Example 16 <Preparation of negative electrode material> was the same as in Example 15, except that the mass ratio of the base material to the amorphous carbon was 82:18.
[0090] Example 17 <Preparation of negative electrode material> was the same as in Example 15, except that the mass ratio of the base material to the amorphous carbon was 70:30.
[0091] Example 18 <Preparation of negative electrode material> was the same as in Example 15, except that the mass ratio of the base material to the amorphous carbon was 55:45.
[0092] Example 19 The procedure is the same as in Example 1, except for the difference in <Preparation of negative electrode material>. The negative electrode material obtained in Example 1 was used as the substrate, and the substrate and polymer carboxymethyl cellulose were dispersed in absolute ethanol at a mass ratio of 99:1. The dispersion was uniformly stirred at room temperature, and then the absolute ethanol was removed to obtain a solid. The obtained solid was pulverized and sieved to obtain a negative electrode material.
[0093] Example 20 <Production of negative electrode material> Odor The same procedure as in Example 19 was used, except that polyacrylic acid was used as the polymer and the mass ratio of the substrate to the polymer was 95:5.
[0094] Example 21 The procedure was the same as in Example 19, except that in <Preparation of negative electrode material>, polyamide was used as the polymer and the mass ratio of the base material to the polymer was 90:10.
[0095] Comparative Example 1 In <Preparation of negative electrode material>, the procedure was the same as in Example 1, except that SiO was not heat-treated in argon gas having an oxygen content of less than 5% by volume.
[0096] Comparative Example 2 In <Preparation of negative electrode material>, the procedure was the same as in Example 1, except that the treatment temperature and treatment time were adjusted to set A / B to 1.33.
[0097] Comparative Example 3 In <Preparation of negative electrode material>, the procedure was the same as in Example 6, except that SiO was not heat-treated in argon gas having an oxygen content of less than 5% by volume.
[0098] Comparative Example 4 The procedure is the same as Comparative Example 1, except for the difference in <Preparation of negative electrode material>. The negative electrode material obtained in Comparative Example 1 was used as the base material, and the base material, amorphous carbon, and carboxymethyl cellulose as a dispersant were dispersed in anhydrous ethanol in a mass ratio of 96:3.2:0.8, and the mixture was stirred uniformly at room temperature, after which the anhydrous ethanol was removed to obtain a solid. The obtained solid was pulverized and sieved to obtain a negative electrode material.
[0099] See Tables 1, 2, 3, 4, 5, 6, 7, 8, 9 and 10 for the production parameters and measurement data of each of the examples and comparative examples. [Table 1]
[0100] [Table 2]
[0101] [Table 3]
[0102] [Table 4]
[0103] [Table 5]
[0104] [Table 6]
[0105] [Table 7]
[0106] [Table 8]
[0107] [Table 9]
[0108] [Table 10]
[0109] As can be seen from Examples 1, 2, and 3 and Comparative Examples 1 and 2, when the silicon monoxide particles are all micron-scale, with the increase in the oxygen content on the surface of the negative electrode material, the cycle performance of the lithium ion battery gradually improves and the swelling of the lithium ion battery gradually decreases, which indicates that the lithium ion battery with the negative electrode material of the present invention has improved cycle performance and swelling resistance.
[0110] As can be seen from Examples 4 and 5, the Dv50 of silicon monoxide affects the cycle performance and expansion rate of a lithium ion battery. However, by setting the Dv50 of silicon monoxide within the range of the present invention, the cycle performance and expansion resistance of the lithium ion battery can be improved.
[0111] As can be seen from Examples 6, 7, 8, 9 and Comparative Example 3, when the silicon monoxide particles are all nanoscale, the lithium ion battery having the anode material of the present invention has improved cycle performance and expansion resistance at 25° C., and improved expansion resistance at 45° C. As can be seen from Examples 6, 9 and Comparative Example 3, the lithium ion battery having the anode material of the present invention has improved cycle performance at 45° C.
[0112] As can be seen from Examples 10, 11, 12, 13, and 14 and Comparative Example 4, when the negative electrode material contains a conductive material, the lithium ion battery having the negative electrode material of the present invention has further improved cycle performance and expansion resistance.
[0113] As can be seen from Examples 15, 16, 17, and 18 and Comparative Examples 1 and 2, when the negative electrode material is a silicon monoxide-amorphous carbon composite material, the lithium ion battery of the present invention further improves both the cycle performance and the expansion resistance at 25° C., and improves the cycle performance at 45° C. In addition, it shows that the cycle performance and the expansion resistance of the lithium ion battery tend to be improved with an increase in the carbon content.
[0114] As can be seen from Examples 19, 20, and 21 and Comparative Examples 1 and 2, when the negative electrode materials all contained a polymer, the lithium ion batteries having the negative electrode materials of the present invention further improved the cycle performance and expansion resistance at 25°C, and improved the cycle performance at 45°C.
[0115] Figure 1 is a schematic diagram (i.e., FIB-TEM line scan element distribution map) of the change in the molar ratio of oxygen to silicon of the negative electrode material of Example 7 of the present invention, specifically, a schematic diagram of the change in the molar ratio of oxygen to silicon measured with the change in the extension distance when the negative electrode material extends from an internal point at a distance of 25 nm from the surface to the outside. As can be seen from Figure 1, the molar ratio of oxygen to silicon of the silicon monoxide particles gradually increases from the inside to the surface, forming a gradient.
[0116] Fig. 2 is a schematic diagram (i.e., FIB-TEM line scan element distribution map) of the oxygen to silicon molar ratio of the negative electrode material of Comparative Example 1 with the change in extension distance, specifically, a schematic diagram of the oxygen to silicon molar ratio measured when the negative electrode material extends from an internal point 25 nm away from the surface to the outside. As can be seen from Fig. 2, the silicon monoxide particles have no regularity in the distribution of the oxygen to silicon molar ratio from the inside to the surface.
[0117] From the above, the lithium ion battery having the negative electrode material of the present invention has improved cycle performance and expansion resistance.
[0118] The above are only preferred embodiments of the present invention, and are not intended to limit the present invention. Any modifications, equivalent changes, improvements, etc. made within the spirit and principles of the present invention are included in the scope of protection of the present invention.
Claims
1. Contains silicon monoxide particles, a molar ratio A of oxygen to silicon on the surface of the silicon monoxide particle and a molar ratio B of oxygen to silicon at any point that is 25 nm or more away from the surface of the silicon monoxide particle satisfy A / B≧2.
17.
2. 2. The negative electrode material according to claim 1, wherein a molar ratio B of oxygen to silicon inside the silicon monoxide particle satisfies 0.5≦B≦1.
5.
3. A conductive material is further present on the surface of the silicon monoxide particles, The conductive material has a thickness of 1 nm to 50 nm; The conductive material includes at least one of amorphous carbon, carbon nanotubes, graphene, and vapor-deposited carbon fibers; 2. The negative electrode material of claim 1, wherein the mass percentage of the conductive material is 0.5% to 8%, based on the total mass of the negative electrode material.
4. A polymer is further present on the surface of the silicon monoxide particles, Based on the total mass of the negative electrode material, the mass percentage of the polymer is 1% to 10%; 2. The negative electrode material of claim 1, wherein the polymer comprises at least one of carboxymethyl cellulose, polyacrylic acid, polyethylene alcohol, polyamide, polyacrylate, and derivatives thereof.
5. 2. The negative electrode material of claim 1, wherein the silicon monoxide particles have a Dv50 of 1 μm to 15 μm.
6. 10. The negative electrode material of claim 1, further comprising amorphous carbon.
7. The negative electrode material is (a) the negative electrode material has a Dv50 of 3 μm to 15 μm; (b) the negative electrode material has a Dv99 of 10 μm to 45 μm; (c) the Dv50 of the silicon monoxide particles in the negative electrode material is 60 nm to 500 nm; And, (d) the capacity per gram of the negative electrode material at 2.0 V is 600 mAh / g to 14 00mAh / g; (e) the mass percentage of carbon is 5% to 50% based on the total mass of the negative electrode material; (f) a mass percentage of silicon is 15% to 38%, based on a total mass of the negative electrode material.
8. A negative electrode piece comprising the negative electrode material according to any one of claims 1 to 7.
9. An electrochemical device comprising the anode piece of claim 8.
10. An electronic device comprising the electrochemical device of claim 9.
Citation Information
Patent Citations
Nonaqueous electrolyte battery
JP2005085717A
Negative-electrode active material for nonaqueous electrolytic secondary battery, negative electrode material, manufacturing method thereof, lithium ion secondary battery, and electrochemical capacitor
JP2013258032A
Anode active material for lithium secondary batteries, lithium secondary battery containing the same, and method for producing the anode active material
JP2015534240A
Porous silicon-based negative electrode active material, manufacturing method thereof, and lithium secondary battery including the same
JP2016509339A
Anode material, and electrochemical device and electronic device using the same
JP2022504017A
